STUDI ATAS BEBERAPA PEMIKIRAN BINT AL-SYATI’ TENTANG KEMUKJIZATAN ALQURAN (Menyorot Sosok Perempuan; Mewujudkan Kesetaraan) - Hamiruddin, Hamiruddin (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2015)
Kemukjizatan study of the Koran is one important aspect of the contemporary scholars in discussing the Quranic sciences are no exception Bint al-Syati '. She is the only female writer who makes the modern sciences of the Qur'an as one of the objects kaijannya. But unlike other contemporary scholars, because Bint Al-Syati 'in theory still rests on balaghah as aspects on the Koran's miraculous.